America's new swing region changing politics and demographics in the Mountain West - Teixeira, Ruy A. (Washington, D.C. Brookings Institution, 2012)
"Analyzes effects of the increase in minorities, younger residents, educational levels, and urbanization on the traditionally Republican politics of six states in the Mountain West, comparing changes in voting patterns from 1988 to 2008. Discusses possible ramifications of those changes and the 2010 mid-term elections on the 2012 presidential election"--Provided by publisher.
Introduction: America's new swing region / Ruy Teixeira -- America's new swing region: the political demography and geography of the Mountain West / William H. Frey and Ruy Teixeira -- Metropolitan voting patterns in the Mountain West: the new and old political heartlands / Robert E. Lang and Thomas W. Sanchez -- Hispanics, race, and the changing political landscape of the United States and Mountain West / William H. Frey -- The political attitudes of the millennial generation in the Mountain West / Scott Keeter -- The Mountain West today: a regional survey / Karlyn Bowman and Ruy Teixeira -- Reapportionment and redistricting in the Mountain West / David F. Damore.
Keywords: Party affiliation -- Rocky Mountains Region; Demography -- Political aspects -- Rocky Mountains Region; Population geography -- Political aspects -- Rocky Mountains Region; Apportionment (Election law) -- Rocky Mountains Region; Rocky Mountains Region -- Politics and government